2017
DOI: 10.21608/epx.2017.16405
|View full text |Cite
|
Sign up to set email alerts
|

Work-related and ergonomic risk factors associated with low back pain among bus drivers

Abstract: Background: Low back pain (LBP) is the commonest form of work-related musculoskeletal disorders, which cause huge economic losses to individuals as well as to the community. Bus drivers have been found to be at an increased risk of LBP owing to several factors associated with physical and occupational circumstances. There is scant knowledge on the problems of LBP among bus drivers in Egypt. Aim: To identify the prevalence of LBP among bus drivers and to determine the ergonomic and occupational risk factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 24 publications
2
39
0
2
Order By: Relevance
“…There is an inconsistent association with general MSP; of the two studies [ 91 , 95 ], one reported no association [ 91 ] and the other a positive association [ 95 ]. A similar inconsistent association was reported with LBP; two studies [ 90 , 99 ] reported a positive association and one study [ 81 ] reported no association. In a meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…There is an inconsistent association with general MSP; of the two studies [ 91 , 95 ], one reported no association [ 91 ] and the other a positive association [ 95 ]. A similar inconsistent association was reported with LBP; two studies [ 90 , 99 ] reported a positive association and one study [ 81 ] reported no association. In a meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Five occupational category cross-sectional studies of bus drivers [ 90 , 95 , 99 ] and professionals (patrol duty police officers) [ 81 , 91 ] reported vehicle time and LBP [ 81 , 90 , 99 ] or general MSP [ 91 , 95 ], including three of high-quality [ 81 , 91 , 99 ]. There is an inconsistent association with general MSP; of the two studies [ 91 , 95 ], one reported no association [ 91 ] and the other a positive association [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a preponderance of male in both groups, presumably, due to the manual handling demands of these jobs. Similarly, higher proportion of male workers have been reported in other jobs requiring manual material handling such as construction work [28,29], commercial driving [30,31], and farming [32]. Among the SWD, significant associations were observed between general WMSS and each of gender, work frequency, and diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 94%
“…Labor-related variables were employment status (“employer”, “self-employed”, “regular employee”, and “non-regular employee”) [ 22 ], income level (low: <4 million JPY; intermediate: 4–7 million JPY; high: >7 million JPY; and unknown or no answer) [ 20 ], and working time (<35, 35–39, 40–44, or >45 h/week) [ 23 ]. We adjusted for health-related status as follows: smoking status (never, former, and current), alcohol use (never, former, and current), and comorbidities (hypertension, diabetes, asthma, chronic obstructive pulmonary disease, cardiovascular disease, stroke, cancer, and psychiatric disorders) [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%